2006
DOI: 10.1007/s10765-006-0135-1
|View full text |Cite
|
Sign up to set email alerts
|

Thermal and Electrical Properties of a Suspended Nanoscale Thin Film

Abstract: This paper reports on measurements of in-plane thermal conductivities, electrical conductivities, and Lorentz number of two microfabricated, suspended, nanosized thin films with a thickness of 28 nm. The effect of the film thickness on the in-plane thermal conductivity is examined by measuring other nanofilm samples with a thickness of 40 nm. The experimental results show that the electrical conductivity, resistance-temperature coefficient, and in-plane thermal conductivity of the nanofilms are much smaller th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 18 publications
1
16
0
Order By: Relevance
“…It has been shown that many material properties such as electrical, optical, and thermodynamic are affected if a material's dimensions are reduced to the nanoscale [25]- [29]. Also, experimental evidence has recently shown that the electrical resistance of thin-film conductors in general or thin-film platinum RTDs in particular do not behave exactly as bulk materials [30]- [33]. Since it is well known that the mean free path of electrons in nanosized materials is smaller compared to electrons in bulk materials [34]- [36], care must be taken if the expression in (6) is used to determine the electrical resistivity of conductors when they are not in bulk form.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that many material properties such as electrical, optical, and thermodynamic are affected if a material's dimensions are reduced to the nanoscale [25]- [29]. Also, experimental evidence has recently shown that the electrical resistance of thin-film conductors in general or thin-film platinum RTDs in particular do not behave exactly as bulk materials [30]- [33]. Since it is well known that the mean free path of electrons in nanosized materials is smaller compared to electrons in bulk materials [34]- [36], care must be taken if the expression in (6) is used to determine the electrical resistivity of conductors when they are not in bulk form.…”
Section: Discussionmentioning
confidence: 99%
“…In Figure 4.7, as expected, the electrical resistance increases with increasing the heating current from 11 to 18 mA. At a current of 18 mA, we estimate the maximum temperature to be [390 K], based on the temperature coefficient of thin film gold (0.0017 K −1 (Zhang et al, 2007)). Above 18 mA we suspect that electromigration occurs.…”
Section: Electrical and Thermal Propertiessupporting
confidence: 70%
“…16. The CNTs were made by an arc-discharge evaporation method and an individual multiwall CNT with a high quality and an available length was selected and fixed to the nanotip of a metallic needle by using local focused electron beam irradiation with the help of a manipulation SEM.…”
Section: A Sample Fabricationmentioning
confidence: 99%